Alemtuzumab induction and sirolimus plus mycophenolate mofetil maintenance for CNI and steroid-free kidney transplant immunosuppression. - Flechner, S; Friend, P; Brockmann, J; Ismail, H; Zilvetti, M; Goldfarb, D; Modlin, C; Mastroianni, B; Savas, K; Devaney, A; Simmonds, M; Cook, D (2005)
We performed a pilot study in which 22 kidney recipients (14 LD: 8 DCD) were given alemtuzumab induction (30 mg day 0 and 1), steroids (500 mg mp day 0 and 1, none thereafter), mycophenolate mofetil (MMF) maintenance (500 mg b.i.d) and sirolimus (concentration controlled 8-12 ng/mL). With a mean follow-up of 15.9 months, patient survival is (21/22) 96% and graft survival (19/22) 87%. Acute rejections occurred in (8) 36.3% (two humoral). Of 19 surviving grafts, 18 (95%) remain steroid and 15 (79%) CNI-free. At 1 year, mean creatinine was 1.43 mg/dL. Overall infection rates were low, but 2 patients developed severe acute respiratory distress syndrome (ARDS) at month 3 and 7, respectively, resulting in mortality in one and a graft loss in the other. No cancer or PTLD was observed. Leukopenia was common and MMF dose was reduced or eliminated in 6/22 (27%) patients. The reported higher than expected rate of acute rejection, leukopenia and possible pulmonary toxicity suggests excessive morbidity. Modifications such as an initial period of CNI use should be considered.